Special metabolites isolated from Urochloa humidicola (Poaceae) - OLIVEIRA,DÉBORA R. DE (2017)
ABSTRACT This study aims to identify special metabolites in polar extracts from Urochloa humidicola (synonym Brachiaria humidicola) that have allelopathic effects and induce secondary photosensitization in ruminants. The compounds were isolated and identified via chromatographic and spectroscopic techniques. The compounds 4-hydroxy-3-methoxy-benzoic acid, trans-4-hydroxycinnamic acid, and p-hydroxy-benzoic acid; the flavonols isorhamnetin-3-O-β-d-glucopyranoside and methyl quercetin-3-O-β-d-glucuronate; and kaempferitrin, quercetin-3-O-α-l-rhamnopyranoside, and tricin were identified in the extract from the leaves of Urochloa humidicola. Two furostanic saponins, namely, dioscin and 3-O-α-l-rhamnopyranosyl-(1-4)-[α-l-rhamnopyranosyl-(1-2)]-β-d-glucopyranosyl-penogenin, as well as catechin-7-O-β-d-glucopyranoside were identified in the methanolic extract obtained from the roots of this plant. This species features a range of metabolites that may be toxic for animals if used in food and may interfere with the growth medium, thereby inhibiting the development of other species.